Processes and patterns in the development and maintenance of stepparent-stepchild relationships - Hadfield, Kristin (Trinity College (Dublin, Ireland). School of Psychology, 2015)
This thesis is an investigation of the processes underlying the development and maintenance of stepparent-stepchild relationships and the patterns that characterize these relationships. Underlying the conceptual focus on relationships within stepfamilies is a substantial body of research which has highlighted the significance of family processes as a mediator of outcomes within diverse family structures, and specifically that the development of a close stepparent-stepchild relationship is important to both child and family outcomes. This study was guided by several theoretical frameworks which conceptualise children and parents as active agents within the family, and which characterize the lives of those in stepfamilies as unstable and uncertain.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin